Entrepreneurship development in Russia: is Russia a normal country? An empirical analysis - Szerb, László; Trumbull, William N (Journal of small business and enterprise development, 2018)
Purpose Using various macro-level measures of economic and political performance Shleifer and Treisman (2005) and Treisman (2014) call Russia a “normal country” implying that Russia’s economic and political development is not deviating from the other middle-income or transition countries significantly. The purpose of this paper is to challenge this proposition and investigate whether Russia is a normal country in terms of entrepreneurship by comparing Russia with other post-socialist and similarly developed countries. Design/methodology/approach Many studies have examined Russia’s institutional setup to explain its deficiencies in entrepreneurial activity. However, there is a lack of comprehensive research taking into account both the individual and institutional dimensions of the entrepreneurial ecosystem. The authors use the Global Entrepreneurship Index (GEI) methodology to analyze Russia’s quality-related individual as well as institutional features from a system perspective in a single model. Findings Russia’s performance has been poor relative to the post-socialist countries and to most of the former republics of the Soviet Union. Russia’s entrepreneurial profile is different from other transition and similarly developed non-transition countries, as well. Russia’s scores are less than the scores of other post-socialist countries in six out of the nine pillars of entrepreneurial attitudes and abilities. In sum, conditions supporting entrepreneurship in Russia lag seriously behind other post-socialist countries. Moreover, Russia’s individual scores are even lower than the institutional ones. Hence, improving the hostile environment alone would not be sufficient for entrepreneurship development. Originality/value Although, there have been numerous studies analyzing Russia’s macroeconomic conditions, institutional development, and entrepreneurship, there is lack of comprehensive studies. Besides common macro-level measures, the authors use a unique, GEI data set that combines institutional factors relating to entrepreneurship or new business creation with measures of individual capabilities, motivations, and attitudes about entrepreneurship. The single-model framework reveals that individual factors are even greater obstacles to entrepreneurship development in Russia than the institutional factors that most studies focus on.